1995
DOI: 10.1093/oxfordjournals.annonc.a059244
|View full text |Cite
|
Sign up to set email alerts
|

Nodular type of lymphocyte predominant Hodgkin’s disease. A clinical study of 50 cases

Abstract: The diffuse variant of LP-HD is rare, having not been seen at St. Bartholomew's Hospital during this time period. The 50 cases with N-LP-HD showed a favourable course with presentation at an early stage, good response to treatment, late recurrences and remission duration other than the other subtypes of HD. The latter could be attributable to the early stage at presentation of N-LP-HD, since the remission duration on a matching on stage analysis was superficially better in favour of N-LP-HD (p = 0.06). The ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…21 Although some groups 6,8,18 have observed late recurrences in patients with nodular LPHD, other groups [22][23][24] have not. In the current study, the histologic subtype of LPHD was not specified in 21% of patients; in addition, diffuse architecture was confirmed in only 4% of patients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…21 Although some groups 6,8,18 have observed late recurrences in patients with nodular LPHD, other groups [22][23][24] have not. In the current study, the histologic subtype of LPHD was not specified in 21% of patients; in addition, diffuse architecture was confirmed in only 4% of patients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…2,11 To our knowledge to date, few large studies with long-term follow-up have been reported for patients with LPHL who were treated with limited RT alone. 2,6,8,9,[12][13][14][15][16] The objectives of the current study were to examine the long-term results of initial RT alone, to identify favorable patient subsets, and to explore the effect of reducing RT field size on treatment efficacy.…”
mentioning
confidence: 99%
“…About two dozen retrospective series have been published in the last three decades characterizing the clinical features of Ͼ1,500 cases of NLPHL (Table 2) [19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The reliability of clinical observations in many of the early studies, however, is uncertain, as many included patients that would likely now be reclassified as having lymphocyte-rich classical Hodgkin lymphoma (LRCHL) or other diseases.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Representative histologies are displayed in Figure 1. Of note, in studies of NLPHL incorporating central pathologic review, up to half the cases were ultimately assigned a different diagnosis, illustrating the difficulty in pathologic interpretation of this disease [19,23,27,30,33,34,41].…”
Section: Histopathologic Featuresmentioning
confidence: 99%
See 1 more Smart Citation